1998
DOI: 10.1111/j.1469-7998.1998.tb00013.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of Cryptosporidium species in Skomer bank voles (Clethrionomys glareolus skomerensis)

Abstract: A survey of Skomer voles (Clethrionomys glareolus skomerensis) conducted in August of 1994 and 1995 discovered that 51% of live-trapped animals were positive for Cryptosporidium species (Coccidia). Of the positive animals, 85% were shedding C. muris in their faeces, 5% C. parvum and 10% apparently both parasite species. On the U.K. mainland, the prevalence of Cryptosporidium in the bank vole (Clethrionomys glareolus) is a quarter of that on Skomer and the species normally found is C. parvum. Interest in C. par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…Overall, populations of red squirrels in Gran Paradiso showed a medium to high infection of C. parvum, with a peak at Rhemes in 2000 (>60%), one of the highest values reported in the literature for wild mammals (Chalmers et al 1995;Bull et al 1998;Sturdee et al 1999;Torres et al 2000), suggesting that this rodent may represent a significant reservoir of Cryptosporidium in alpine forests. In Gran Paradiso the prevalence of C. parvum was higher at Rhemes than at Cogne and decreased from 2000 to 2001.…”
Section: Diversity and Stability Of Coccidian Communitiesmentioning
confidence: 82%
“…Overall, populations of red squirrels in Gran Paradiso showed a medium to high infection of C. parvum, with a peak at Rhemes in 2000 (>60%), one of the highest values reported in the literature for wild mammals (Chalmers et al 1995;Bull et al 1998;Sturdee et al 1999;Torres et al 2000), suggesting that this rodent may represent a significant reservoir of Cryptosporidium in alpine forests. In Gran Paradiso the prevalence of C. parvum was higher at Rhemes than at Cogne and decreased from 2000 to 2001.…”
Section: Diversity and Stability Of Coccidian Communitiesmentioning
confidence: 82%
“…Wildlife species, including deer (19) raccoons (24), squirrels (2), chipmunks (19), bank voles and other wild rodents (6,7,26), and birds (11), have been identified as significant sources of Cryptosporidium contamination in watersheds. Further, many of these wildlife host species have been implicated in transmission cycles involving zoonotic Cryptosporidium species (2,5,19).…”
mentioning
confidence: 99%
“…For instance, some studies showed that the prevalence of cryptosporidiosis in calves and cattle was higher in winter (Garber et al 1994;Mohammed et al 1999). According to Bull et al (1998) and Torres et al (2000) reports in wild animals, the prevalence of cryptosporidiosis was not age depended. On the other hands, in Iran, some studies found significant relationship among Cryptosporidium infection and age (Gharekhani et al 2014;Heidarnegadi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For innate and large scale studies, microscopy is more successful method when combined with concentration techniques and staining of fecal smears with appropriate stain and well modification of the procedure since there are many particles in fecal specimens that may confuse the microscopists. With this regards, modified Ziehl-Neelsen method is mentioned as a reasonably useful tool to distinguish the Cryptosporidium (Bull et al 1998;De Quadros et al 2006;Thompson et al 2007;Fayer and Xiao 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation